COVID-19 vaccine hesitancy in health care workers - Pradhananga, Sneha; Shrestha, Trishna; Batajoo, Kabita Hada; Pandey KC, Bindu; Shrestha, Roshan (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Vaccination is one of the best ways to flatten the curve of COVID 19 infection and success of vaccination is achieved when vaccine hesitancy is minimal. The aim of this study is to analyze reasons for vaccine hesitancy among health care workers of a tertiary care hospital in Kathmandu Valley scheduled for COVID-19 vaccination.Method: This is a descriptive cross sectional study conducted at KIST Medical College and Teaching Hospital from 25th February 2021 to 15th March 2021.This study included 156 health care workers of KIST Medical College who did not opt for the first dose of vaccination for COVID-19.Result: The majority of health care workers hesitant for vaccination belonged to age group 18-29 years 67(42.9%)and females 117(75%) were more hesitant to vaccine than males. Helper and cleaning staffs 45(28.8%) were found to be more hesitant for vaccination followed by nursing staffs 29(18.6%). The reasons for vaccine rejection were due to safety issues 65(41.7%), followed by willingness to get vaccination at a later date 17(10.9%), misunderstanding the need of vaccination if already infected 14(8.9%), planning for pregnancy 14(8.9%), lactating mothers 14(8.9%) and pregnancy 11(7.1%).Conclusion: This study emphasizes on the need of more advocacies in the safety of Covid19 vaccination. Its safety during pregnancy and lactation is to be addressed to increase the vaccination rate.